ANALISIS FAKTOR RENDAHNYA MINAT BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS VI SD - Alda Baringbing; Antonius Remigius Abi; Patri Janson Silaban (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article discusses the analysis of students’ low interest as the factor in mathematics learning subjects. Research method used was a qualitative method with the approach of a case study to produce descriptive data in the form of written or spoken words from the subject or actor and observed behaviour. Purpose of the study was to discover in-depth and try to find out the meaning that underlied the students' interest in mathematics learning subjects. The informant in the interviews involved seven people, three students as main informants who had low math scores, three parents, and one homeroom teacher at the sixth-grade level of SDN 038095 Barisan Sirait Sinehi Dairi. To find out the factors of students’ low interest in mathematics learning subjects, the researcher conducted direct observations and interviews. After achieving the results of interviews, the researchers obtained information that students who had a low interest in mathematics learning subjects were influenced by a number of factors. They were (1) students' time off who was less at home, (2) students who were not interested in mathematics learning subjects, (3) parents who never helped students in learning, (4) students' fear of asking the teacher, (5) media and learning tools that were never used in class, (6) parents who never accompanied students to learn mathematics, and (7) students who did not know how to develop their own interests.